THE ROLE OF MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Jamali, Hisnol; Ibrahim, Ibrahim; Horas, Erwin; Haeruddin, Haeruddin (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study examines the effect of motivation and organizational culture on the performance of employees of the Makassar Customs Inspection and Service Board. With a sample of 96 respondents, data analysis was performed using multiple linear regression. The results show that motivation and organizational culture have a significant impact on individual and collective performance. These findings confirm the central role of motivation and organizational culture in growing staff, especially in the customs and excise sector. The holistic approach of this study combines these key variables and provides a comprehensive view of the variables that influence employee performance. The significance of this research focuses on the need to improve the efficiency of the public sector, while its impact includes practical guidance for organizational managers and a contribution to advanced research in the field of public HRM.